2015
DOI: 10.4141/cjps-2014-264
|View full text |Cite
|
Sign up to set email alerts
|

Biologically effective rate of sulfentrazone applied pre-emergence in soybean

Abstract: . 2015. Biologically effective rate of sulfentrazone applied pre-emergence in soybean. Can. J. Plant Sci. 95: 339Á344. Sulfentrazone is a protoporphyrinogen (PPO)-inhibiting herbicide under evaluation for use in soybean in Ontario, Canada. The primary objective of this study was to determine the dose of sulfentrazone applied pre-emergence (PRE) needed to provide 50 and 90% control of redroot pigweed, common ragweed, common lambsquarters and green foxtail. Seven field trials were conducted over a 3-yr period (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
4
12
0
5
Order By: Relevance
“…All herbicides and herbicide combinations reduced pigweed density and biomass by 91% to 100% and 86% to 100%, respectively, and were not different from the weed-free control. This is consistent with other studies which found excellent control of redroot pigweed with sulfentrazone at similar rates [14] [15].…”
Section: Pigweed Speciessupporting
confidence: 82%
See 1 more Smart Citation
“…All herbicides and herbicide combinations reduced pigweed density and biomass by 91% to 100% and 86% to 100%, respectively, and were not different from the weed-free control. This is consistent with other studies which found excellent control of redroot pigweed with sulfentrazone at similar rates [14] [15].…”
Section: Pigweed Speciessupporting
confidence: 82%
“…provided up to 81% control of barnyard grass ( Table 6). Wilson et al [14] also noted that sulfentrazone at these rates provided up to 78% control of barnyard grass. S-metolachlor provided 100% control and imazethapyr alone controlled barnyard grass by 69%.…”
Section: Wild Mustardmentioning
confidence: 99%
“…In fact, there is several evidences that herbicide detoxification is responsible for many cases of tolerance of crop plants to herbicides, including corn to nicosulfuron (Liu et al, 2015), cotton to pyrithiobac (Snipes and Seifert, 2003), corn to mesotrione (Ogliari et al, 2014), and soybean to sulfentrazone (Walsh et al, 2015). There is evidence of tolerance of common bean to other ALS inhibitors (Procopio et al, 2009).…”
Section: Tolerance Mechanismmentioning
confidence: 99%
“…While Walsh et al (2015) reported 90% control of common lambsquarters with only 133 g a.i. ha (1 pyroxasulfone, more than three times the highest rate evaluated in this study, was needed to provide the same control (90%).…”
mentioning
confidence: 99%
“…(Dayan et al 1996;Niekamp et al 1999;Dirks et al 2000). Although excellent weed control (90%) has been reported for sulfentrazone, level of control was dependent upon weed community composition (Walsh et al 2015).…”
mentioning
confidence: 99%